2018
DOI: 10.5430/jnep.v8n7p113
|View full text |Cite
|
Sign up to set email alerts
|

Upright versus recumbent position during first stage of labor among primipara women on labor outcomes

Abstract: Objective: The aim of this study was to assess the effect of upright versus recumbent position during the active phase of first stage of labor among primipara women on labor outcomes in term of progress, duration of labor, method of delivery, neonatal outcome and maternal satisfaction with assumed position.Methods: Quasi experimental design was used. The study was conducted in the labor unit in obstetric department at Benha University Hospital. A purposive sample of 100 parturient women in 1st stage of labor w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
19
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(26 citation statements)
references
References 12 publications
3
19
0
4
Order By: Relevance
“…It is also in accordance with the previously mentioned one done by Emam and Eidah Al-Zahrani (2018) (Emam & Al-Zahrani, 2018) who revealed that high statistical significant difference between the squatting and recumbent groups in term of decreases duration of the three stages of labor among the upright group. In addition, it is relatively congruent with Moralogluetal (2017) (Moraloglu et al, 2017)who revealed that women experienced a significant reduction in the duration of the second stage of labor with the mean length of the second-stage of labor shorter in the squatting group than in the supine group.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…It is also in accordance with the previously mentioned one done by Emam and Eidah Al-Zahrani (2018) (Emam & Al-Zahrani, 2018) who revealed that high statistical significant difference between the squatting and recumbent groups in term of decreases duration of the three stages of labor among the upright group. In addition, it is relatively congruent with Moralogluetal (2017) (Moraloglu et al, 2017)who revealed that women experienced a significant reduction in the duration of the second stage of labor with the mean length of the second-stage of labor shorter in the squatting group than in the supine group.…”
Section: Discussionsupporting
confidence: 92%
“…Moreover it increase the size of pelvic diameter by approximately 20% thereby enabling faster labor progress , as well as maternal expulsive forces facilitated by the force of gravity , improved alignment of the fetus for passage through the pelvis. (Zwelling, 2010) This result is relatively coincides with the study of Emam A, Eidah Al-Zahrani (2018) (Emam & Al-Zahrani, 2018)who showed that decrease interval and increases duration, frequency and intensity of uterine contraction were found among squatting group compared to of the recumbent group. Furthermore the result is in harmony with Gizzo SS et.al.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…The latter had clarified that the ambulation in the first stage of labor results in increase of the quality of uterine contractions. 18,19 Moreover, upright position and ambulation during active first stage of labor appear to be effective in improving the progress of cervical dilatation, and fetal head descent in the study group compared with control group. This can be attributed to the fact that upright positions allow the gravity to assist in the descent of the fetal head, as well as increase the pelvic capacity giving the baby more room to descend and rotate.…”
Section: Discussionmentioning
confidence: 88%
“…In the first one, Emam indicated a significant difference between upright and recumbent groups in relation to fetal head descent and cervical dilatation progress in favor of the upright group. 18 In the second study, Hassan had reported a significant improvement in the progress of fetal head descent and cervical dilatation in the experimental group after performing the pelvic rocking exercise using sitting position during the active phase of the first stage of labor as compared with the control group. 22 In the third study, Lawrence et al who had done a Cochrane review on 25 studies to evaluate the effect of ambulation and upright positions in the first stage of labor, recognized that upright positions were more effective in the cervical dilation progress than supine position.…”
Section: Discussionmentioning
confidence: 97%